Flora indígena de cucarachas (Dictyoptera: Blattidae y Blattellidae): un análisis bacteriológico y ultraestructural - Sánchez, Claudio (1994)
Intradomiciliary cockroaches (Periplaneta americana Linnaeus 1753), P. australasiae Fabricius 1775), and Blattella germanica Linnaeus 1767) were collected in a Day Care Center (CEN-CINAI) and four foodstores of the Central Market, San José, Costa Rica. Enterobacter aerogenes, E. agglomerans, E. gergoviae, Citrobacter freundi, Klebsiella pneumoniae, K. oxytoca, Hafnia alvei, and Pseudomonas sp. were isolated from bodywash of the insects and from their intestinal contents. Scanning electron microscopy observations of the body and negative staining specimens of intestinal contents and ultrathin sections of intestine show abundant morphotypes of bacteriae, include bacilli and curve-shaped rods, some of them with periplasmic fibers.